Catalytic Steam Reforming of Toluene for Hydrogen Production over Nickel-Cobalt Supported Activated Carbon - Mohidin Yahya, Hamdya Sabrina; Saidina Amin, Nor Aishah (International Journal of Integrated Engineering, 2019)
Hydrogen may play a key role in future sustainable energy system as a carrier of renewable energy to replace the conventional fossil fuel. Biomass gasification is the most promising method in renewable hydrogen production technologies. However, the tar by-product poses great obstacle in the realization of commercial biomass gasification. In this work, the performance of Ni and/or Co supported on modified-palm kernel shell-derived activated carbon (AC) catalyst in steam reforming of toluene (SRT) for the production of hydrogen has been investigated. Toluene has been chosen as a model compound since it represents one of the major tar compositions. The effects of nitric acid in the surface pretreatment of AC (ACN) and the influence of Ni and/or Co loading on the catalyst support are studied. The catalysts are characterized using FTIR, BET, XRD, TGA and FESEM-EDX. The modified-AC support shows that the surface area, microporous structure and surface oxygenated functional group (SOFG) increase, leading to a homogeneous distribution of metal particles. The highest toluene conversion (Xtoluene) and hydrogen yield (YH2) obtained over 10%Ni-10%Co/ACN are 70% and 69%, respectively. The catalytic performance of bimetallic Ni–Co/ACN catalyst is more significant compared to monometallic Ni- and Co-supported catalysts. The highest catalytic performance achieved can be attributed to the larger surface area and unique porous structure of the modified-AC support as well as the formation of Ni–Co solid solution alloys that improve its coke-resistant capability with low carbon formation during SRT. The modified palm kernel shell AC-supported bimetal catalyst has high potential as a biomass-based catalyst for the applications in biomass tar removal toward hydrogen production due to its good coke-resistance properties.